Renal Biomarkers for Treatment Effect of Ranibizumab for Diabetic Macular Edema - Ivan Pochou Lai; Wei-Lun Huang; Chung-May Yang; Chang-Hao Yang; Tzyy-Chang Ho; Yi-Ting Hsieh (Journal of Diabetes Research)
Aims. To investigate the correlations between renal biomarkers and the treatment outcomes of ranibizumab for diabetic macular edema (DME). Methods. This hospital-based study retrospectively enrolled 88 eyes from 67 patients who had received one-year intravitreal ranibizumab treatment for DME. Best-corrected visual acuity (BCVA) and optical coherence tomography (OCT) at baseline and during the follow-up period were recorded. BCVA and OCT characteristics at baseline and their changes after ranibizumab treatment were compared between different proteinuria and estimated glomerular filtration rate (eGFR) groups. Results. Of the 88 eyes studied, those with moderately increased proteinuria had a thicker central subfield foveal thickness (CFT) and a higher proportion of intraretinal cysts than those with no proteinuria (P=0.012 and 0.045, respectively) at baseline. After one year of ranibizumab treatment, the reduction in CFT was greater in patients with severely increased proteinuria than those with normal to mildly increased proteinuria (P=0.030). On the other hand, patients with an eGFR <30 tended to have poorer visual improvements than those with normal eGFR (P=0.044). Conclusions. After ranibizumab treatment for DME, patients with severe proteinuria tended to gain better anatomical improvement, while those with poor eGFR tended to have poorer visual improvement.